A Web-Based Safety Stock Monitoring Information System for Production Materials at CV. Ewelding's Iron Workshop - Nuzul Zainul Wildan; Darmanto, Eko; Nughraha, Fajar (Jurnal Teknologi Informasi dan Pendidikan, 2025)
CV. Ewelding is a metal workshop that experiences difficulties in managing production material stock due to manual processes that result in data discrepancies and the risk of production delays. This study aims to build a web-based stock monitoring information system with a safety stock method to ensure the availability of safe minimum stock. The system development methodology uses the waterfall model, with stages of needs analysis, system design, implementation, testing, and maintenance. The system was developed using PHP and MySQL, and is designed to support customer data management, ordering, material calculations, and production monitoring reports. The implementation results show that the system is able to provide real-time information, assist decision-making, and reduce the risk of material shortages. This system also provides efficiency for business actors in managing overall production operations.